1985
DOI: 10.1002/jmv.1890160303
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of various serological methods and diagnostic kits for the detection of acute, recent, and previous rubella infection, vaccination, and congenital infections

Abstract: The antibody development after natural rubella infection and rubella vaccination has been followed in 802 sera from 493 patients and 71 sera from 22 vaccinees. Also examined were 67 sera from 28 infants with rubella embryopathy and sera from 50 children with presumed prenatal infection. In addition, 777 sera from 641 patients tested for routine rubella diagnosis were studied. Anamnestic information was available from all these patients. These sera were assayed for IgM antibody detection by sucrose density grad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

1985
1985
1991
1991

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 16 publications
0
3
0
1
Order By: Relevance
“…Rubella-specific IgM antibody usually appears 1 to 5 days after the onset of rash, sometimes at the same time as IgG antibodies. IgM antibodies usually persist for 6 to 12 weeks (Enders et al, 1985;Enders and Knotek, 1986;Meurman et aI., 1977), but occasionally for longer. The detection of rubella-specific IgA depends on the test used; it may persist for a number of years (Halonen et al, 1979;O'Shea et al, 1985).…”
Section: Immune Responsesmentioning
confidence: 95%
See 1 more Smart Citation
“…Rubella-specific IgM antibody usually appears 1 to 5 days after the onset of rash, sometimes at the same time as IgG antibodies. IgM antibodies usually persist for 6 to 12 weeks (Enders et al, 1985;Enders and Knotek, 1986;Meurman et aI., 1977), but occasionally for longer. The detection of rubella-specific IgA depends on the test used; it may persist for a number of years (Halonen et al, 1979;O'Shea et al, 1985).…”
Section: Immune Responsesmentioning
confidence: 95%
“…Many laboratories now diagnose rubella by solid phase immunoassays (EIA and RIA). In experienced laboratories, using optimal antigen preparations the RIA and EIA may be one of the most sensitive methods for serologic diagnosis of rubella (Enders et al, 1985;Forghani and Schmidt, 1979;Kalimo et ai., 1976;Vaheri and Salonen, 1980;Vejtorp et al, 1979;Voller and Bidwell, 1975). These methods are so sensitive that testing the serum specimens at several dilutions and expressing the test results in titers is inconvenient.…”
Section: Diagnostic Assaysmentioning
confidence: 99%
“…Vaccine trials have shown that all licensed rubella vaccines induce an antibody response [16,17]. Haemagglutination inhibition (HA1) antibodies usually develop between 10 and 28 days after vaccination [57][58][59], although a response may occasionally be delayed. HAI antibodies are usually 4-8-fold lower in vaccinees than following natural infection.…”
Section: Risks Of Vaccination In Pregnancymentioning
confidence: 99%
“…Die Serumprodem Hämagglutinationshemmtest ist daß mit dem ersteben werden, beginnend bei 1:8, in Zweierstufen in Dexren ein quantitativer Antikörpernachweis nicht möglich trose-Gelatine-Veronal-Puffer austitriert. Danach erfolgt ist (2,3 …”
Section: Introductionunclassified